2010
DOI: 10.3382/ps.2010-00738
|View full text |Cite
|
Sign up to set email alerts
|

Dietary lipid source and vitamin E effect on lipid oxidation stability of refrigerated fresh and cooked chicken meat

Abstract: The fatty acid composition of chicken muscle may affect the lipid oxidation stability of the meat, particularly when subjecting the meat to thermal processing and storage. The objective of this study was to evaluate the diet effect on lipid oxidation stability of fresh and cooked chicken meat. Six hundred broilers were raised for a 6-wk feeding period and were assigned to 8 treatments with 3 repetitions. Broilers were fed a basal corn-soybean meal diet, including 5% of either animal-vegetable, lard, palm kerne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…The present data are in agreement with those of (Koreleski and Swiatkiewicz 2005) who found that at a dietary level of 0.5% or more of fish oil and fish oil plus 300 mg α-tocopheryl acetate, there was an increase of EPA and DHA contribution in breast meat of chickens. In a similar context, Narciso-Gaytán et al (2010) found that the diets supplied with 2% fish oil plus 200 mg/kg of α tocopherol acetate induced the highest deposition of EPA and DHA fatty acids compared to linseed oil plus 200 mg/kg of α-tocopherol acetate. In addition, Voljc et al (2013) concluded that the concentration of EPA (C20:5 n-3) and DHA (C22:6 n-3) in meat samples were increased in 3 g/kg SCT and 200 mg/kg α-tocopherol groups.…”
Section: Discussionmentioning
confidence: 86%
“…The present data are in agreement with those of (Koreleski and Swiatkiewicz 2005) who found that at a dietary level of 0.5% or more of fish oil and fish oil plus 300 mg α-tocopheryl acetate, there was an increase of EPA and DHA contribution in breast meat of chickens. In a similar context, Narciso-Gaytán et al (2010) found that the diets supplied with 2% fish oil plus 200 mg/kg of α tocopherol acetate induced the highest deposition of EPA and DHA fatty acids compared to linseed oil plus 200 mg/kg of α-tocopherol acetate. In addition, Voljc et al (2013) concluded that the concentration of EPA (C20:5 n-3) and DHA (C22:6 n-3) in meat samples were increased in 3 g/kg SCT and 200 mg/kg α-tocopherol groups.…”
Section: Discussionmentioning
confidence: 86%
“…Chicken feeding standards stipulate levels of particular vitamins and nutrients indispensable from the viewpoint of these birds' physiology (Koreleski et al 2005). The administration of the standard amount of vitamin E in diet for chicken was demonstrated not to protect meat lipids against oxidation processes (Coetzee and Hoffman, 2001;Narciso-Gaytán et al 2010). The protection of chicken meat against the loss of valuable components, important for man, requires providing the appropriate level of antioxidants used as dietary extra supplements.…”
Section: Introductionmentioning
confidence: 99%
“…Lipids are not only an important part of energy storage, but are also intimately related with meat quality. A majority of studies indicate that a high content of intramuscular fat improves the tenderness and flavor of raw muscle and cooked muscle (DeVol et al, ; Narciso‐Gaytán et al, ; Wood & Enser, ). The muscle bundle can be dissolved by oxidating intramuscular fat, and intramuscular fat is rich in aroma precursors (fatty acids and phospholipids), which increase muscle flavor by lipid degradation.…”
Section: Discussionmentioning
confidence: 99%